Modeling thiamine fortification: a case study from Kuria atoll, Republic of Kiribati. Issue 1 (12th January 2021) - Green, Tim J.; Whitfield, Kyly C.; Daniels, Lisa; Brown, Rachel C.; Houghton, Lisa A.
Abstract: In 2014, there was an outbreak of beriberi on Kuria, a remote atoll in Kiribati, a small Pacific Island nation. A thiamine‐poor diet consisting mainly of rice, sugar, and small amounts of fortified flour was likely to blame. We aimed to design a food fortification strategy to improve thiamine intakes in Kuria. We surveyed all 104 households on Kuria with a pregnant woman or a child 0–59 months. Repeat 24‐h dietary recalls were collected from 90 men, 17 pregnant, 44 lactating, and 41 other women of reproductive age. The prevalence of inadequate thiamine intakes was >30% in all groups. Dietary modeling predicted that rice or sugar fortified at a rate of 0.3 and 1.4 mg per 100 g, respectively, would reduce the prevalence of inadequate thiamine intakes to <2.5% in all groups. Fortification is challenging because Kiribati imports food from several countries, depending on price and availability. One exception is flour, which is imported from Fiji. Although resulting in less coverage than rice or sugar, fortifying wheat flour with an additional 3.7 mg per 100 g would reduce the prevalence of inadequacy to under 10%. Kiribati is small and has limited resources; thus, a regional approach to thiamine fortification is needed.